PENGARUH BRAND AMBASSADOR NCT 127 TERHADAP PURCHASE DECISION MELALUI BRAND TRUST PADA E-COMMERCE BLIBLI.COM - Hanifa Maulani Ramadhan (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The purpose of this study is to know and explain the influence of Brand Ambassadors on Purchase Decisions through Brand Trust for Blibli.com consumers in Malang City. This type of research uses explanatory research with a quantitative approach. Sampling was carried out by Blibli.com e-commerce users in Malang City with 130 respondents by calculating the Hair (2010) formula using a purposive sampling technique and collecting data through online questionnaires. The analysis carried out in this study was descriptive analysis and path analysis using SPSS 25 for MacBook software. The results of this study indicate that (1) the Brand Ambassador variable has a significant effect on Brand Trust, (2) the Brand Ambassador variable has a significant effect on Purchase Decision, (3) the Brand Trust variable has a significant effect on Purchase Decision, (4) there is an indirect relationship positive relationship between Brand Ambassadors on Purchase Decisions through Brand Trust.